Rescue activity of a civilian helicopter emergency medical service in the western cape, South Africa: a five-year retrospective review - Park-Ross, Jocelyn Frances (Division of Emergency Medicine, 2022)
Introduction - Helicopter search and rescue in Africa is conducted primarily by military organizations. Since 2002 the Western Cape of South Africa has had a dedicated contracted civilian helicopter emergency medical service (HEMS) conducting air ambulance, terrestrial and aquatic rescue. This is the first description of the operations of an African helicopter rescue service. Objective - To describe the terrestrial and aquatic helicopter rescue activity of a civilian operated HEMS in the Western Cape, South Africa from 1 January 2012 – 31 December 2016. Methods - A five-year retrospective review was conducted using data from the organization's operational database, aviation documents, rescue reports and patient care records. Patient demographics and activity at time of rescue, temporal and geographical distribution, crewing compositions, patient injury, triage, clinical interventions and rescue techniques were analysed. Results – A total of 581 search and rescue missions were conducted, of which 451 were terrestrial and 130 aquatic rescues. The highest volume of rescues was conducted within the urban Cape Peninsula. Hoisting using a rescue harness was the most common rescue technique used. 644 patients were rescued. Uninjured or minorly injured persons represented 79% of the sample. Trauma (33%, 196/644) was the most common medical reason for rescue, with lower limb trauma predominant (15%, 90/644). The most common clinical interventions performed were intravenous access (108, 24%), spinal immobilization (92, 21%), splinting (76, 17%) and analgesia administration (58, 13%). Conclusions - The patient demographics and rescue activity described are similar to those described in high-income settings.